ANALYSIS ON VOLUMETRIC SHRINKAGE OF PLASTIC FOOD CONTAINER MADE FROM AN INJECTION MOLDING PROCESS - Rosidah Jaafar; Hambali Arep; Effendi Mohamad; Jeefferie Abd Razak; Muhamad Arfauz A Rahman; Rahmi Yuniarti (Journal of Engineering and Management in Industrial System, 2020)
The plastic injection molding process is one of the widely used of the manufacturing process to manufacture the plastic product with high productivity.  Moreover, the food packaging manufacturing industry undergoes the trials and errors to obtain the optimal setting of the process parameters in order to minimize the quality issues and these trials and errors are time consuming and costly.  The aim of this study is to improve the quality of the butter tub by minimizing the volumetric shrinkage. This study is to deal with the application of Moldflow integrating with the statistical technique to minimize the volumetric shrinkage the butter tub which depends on the process parameters of the plastic injection molding.  For this purpose, the rectangular shape of butter tub is designed by utilizing the SolidWorks.  Molflow is used to simulate the plastic filling of the single cavity mold of butter tub based on the Taguchi’s  orthogonal array table.  In addition, the analysis of variance (ANOVA) is applied to investigate significant impact of the process parameters on the quality of the butter tub. Minitab is used to optimize the response of the volumetric shrinkage by selecting the most appropriate process parameters that maximizing the desirability value.  Furthermore, the butter tub has a uniform thickness which was 1.2 mm and its factor of safety was 3.383 and the volumetric shrinkage response have optimized by 0.956 %. The melt temperature and mold temperature are found to be the most significant process parameters for the plastic injection molding process of butter tub and the volumetric shrinkage value obtained from the simulation is verified by the calculated volumetric shrinkage value.